2003
DOI: 10.4102/jsava.v74i4.525
|View full text |Cite
|
Sign up to set email alerts
|

Epistaxis related to exercise-induced pulmonary haemorrhage in South African Thoroughbreds

Abstract: <span style="font-family: arial,helvetica;">This study investigated if environmental factors had an effect on the incidence of epistaxis related to exercise-induced pulmonary haemorrhage (EIPH) among racehorses in southern Africa. Data covering the period 1986-2001 and involving 778 532 race runs were analysed. This included the following information : date of race, age, sex, name of breeder, trainer, distance, jockey, state of going, weight carried, racing centre and altitude. Veterinarians employed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 12 publications
4
29
1
Order By: Relevance
“…Increasing age has been suggested to be associated with epistaxis in horses, with horses aged ≥5 years being up to 6.4 times more likely to have epistaxis compared to 2‐year‐old horses (Takahashi et al . 2001; Weideman et al . 2003) although neither study controlled for the confounding effect of increased numbers of lifetime starts, which would be expected to be highly correlated with age in most horses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing age has been suggested to be associated with epistaxis in horses, with horses aged ≥5 years being up to 6.4 times more likely to have epistaxis compared to 2‐year‐old horses (Takahashi et al . 2001; Weideman et al . 2003) although neither study controlled for the confounding effect of increased numbers of lifetime starts, which would be expected to be highly correlated with age in most horses.…”
Section: Discussionmentioning
confidence: 99%
“…Studies reporting the assessment of risk factors for EIPH have often used epistaxis as a marker for the disorder (Takahashi et al . 2001; Weideman et al . 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Virtually all horses bred and trained for competitive racing show evidence of exercise-induced pulmonary hemorrhage (EIPH), which manifests as bleeding from the nose after exertion or the presence of red blood cells or hemosiderophages in the airways (3,6,21,39,47,53,58,67). The causative mechanism of EIPH was demonstrated experimentally when it was shown that high pulmonary capillary pressures can cause discrete breaks in the endothelium, epithelium, or the entire BGB in mammals (10,50,64,66).…”
mentioning
confidence: 99%
“…This would involve testing stallions' offspring in an epistaxis-challenging environment. As a clear positive relationship between racing at sea level and epistaxis was established 17 , it might be fruitful to challenge the southern African based sires, comparing all offspring produced that raced at sea level, clearly an unfavourable condition. This may shed more light on the predisposition of imported sires of unknown bleeder status and in some instances racing after treatment with furosemide (Lasix), producing more than their share of offspring that suffer epistaxis.…”
Section: Resultsmentioning
confidence: 99%
“…A variety of findings have been reported. These include a positive relationship between EIPH and age 16 , EIPH and the cooler months of the year 7 , EIPH and sex 12 and EIPH as associated with pulmonary haemorrhage and altitude 17 . On the other hand similar studies could not establish any relationship between EIPH and sex 8 , EIPH and the distance raced 15 , while no association was found between EIPH and trainer or going 9 .…”
Section: Introductionmentioning
confidence: 99%